2013
DOI: 10.3892/mmr.2013.1472
|View full text |Cite
|
Sign up to set email alerts
|

Role of the heme oxygenase/carbon monoxide pathway in the pathogenesis and prevention of hepatic encephalopathy

Abstract: Abstract. Hepatic encephalopathy (HE) is a severe complication of liver cirrhosis and its pathogenesis has yet to be fully elucidated. Previous studies have demonstrated that heme oxygenase-1 (HO-1) is important in the induction of liver cirrhosis. The present study aimed to investigate the role of HO-1 in the pathogenesis of HE. Rats were divided into 5 treatment groups; sham, bile duct ligation (BDL), HE, zinc protoporphyrin (ZnPP) and cobalt protoporphyrin (CoPP). The levels of HO-1 were examined by western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The reasons for these differences results may be that HO-1 exerts different roles during the progression of liver fibrosis ( 43 ) and that protection is restricted to a narrow HO-1 expression threshold ( 44 ). In the early stages of liver fibrosis, low HO-1 induction may exert a protective action ( 45 ), but in the end stages of cirrhosis with portal hypertension, excessive HO-1 expression deteriorates liver function and aggravates liver cirrhosis ( 43 , 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for these differences results may be that HO-1 exerts different roles during the progression of liver fibrosis ( 43 ) and that protection is restricted to a narrow HO-1 expression threshold ( 44 ). In the early stages of liver fibrosis, low HO-1 induction may exert a protective action ( 45 ), but in the end stages of cirrhosis with portal hypertension, excessive HO-1 expression deteriorates liver function and aggravates liver cirrhosis ( 43 , 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, elevated HO-1 protein levels and deranged iron homeostasis are features of the aging brain 19 and overexpression of HO-1 in astrocytes induces senescence 15 and is associated with behavioural abnormalities in mice 20 . Upregulation of HO-1 was also shown in ammonia-treated cultured rat astrocytes 21 , in different animal models for HE 21 22 23 and in post mortem human brain samples of patients with liver cirrhosis and HE 24 . However, whether upregulation of HO-1 contributes to ammonia-induced astrocyte senescence in HE is currently unknown.…”
mentioning
confidence: 84%
“…Interestingly, a recent study showed that systemic application of the HO1 inhibitor Zinc Protoporphyrin (ZnPP) diminished oxidative stress and ameliorated behavioral abnormalities in brain of rats fed with an ammoniumcontaining diet. 53 However, further studies are required to exclude that side effects of ZnPP account for the observed anti-oxidative effects in brain and normalization of behavior in hyperammonemic rats. 53 Besides ammonia, also hypoosmolarity-induced astrocyte swelling triggers ROS formation, 14 upregulation of HO1 37 and senescence 37 in astrocytes.…”
Section: Ho1 and Ammonia-induced Astrocyte Senescencementioning
confidence: 99%
“…53 However, further studies are required to exclude that side effects of ZnPP account for the observed anti-oxidative effects in brain and normalization of behavior in hyperammonemic rats. 53 Besides ammonia, also hypoosmolarity-induced astrocyte swelling triggers ROS formation, 14 upregulation of HO1 37 and senescence 37 in astrocytes. This again underlines the fundamental role of osmotic and oxidative stress in astrocytes for the pathogenesis of HE (Figure 2).…”
Section: Ho1 and Ammonia-induced Astrocyte Senescencementioning
confidence: 99%